Kemampuan Afektif Calon Guru Sekolah Dasar Pada Pembelajaran Online Di Program Studi PGSD Universitas Muhammadiyah Pringsewu Lampung - Yesi Budiarti; Meita Dwi Solviana (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Jember, 2021)
Learning is a conscious effort made by individuals to acquire various kinds of abilities (competencies), skills (skills), and attitudes (attitudes) through a series of learning processes that will ultimately result in behavioral changes in the individual. The learning process in schools tends to emphasize the achievement of changes in cognitive (intellectual) aspects which are carried out through various forms of approaches, strategies, and certain learning models. Learning systems that specifically develop affective abilities have received less attention, affective abilities are only used as a nurturing effect. This study aims to (1) find out whether online learning is able to bring out the affective abilities of prospective study program teachers (2) analyze the affective abilities of prospective teachers in online learning. The data used in this study is qualitative data. The technique used is a questionnaire. This questionnaire was given to respondents, namely students of PGSD teacher candidates at Muhammadiyah University of Pringsewu. The results of the study indicate that affective abilities can appear in online learning as evidenced by the results of the questionnaire that has been given to respondents. The indicators of affective ability in this study include attitudes, interests, self-concept, values, and morals, all of which are in the good range. This means that the results of students' affective abilities can be said to be valid or appear in online learning Keywords: Affective Ability; e-learning; PGSD Belajar merupakan upaya sadar yang dilakukan individu untuk memperoleh berbagai macam kemampuan (competencies), ketrampilan (skills), dan sikap (attitudes) melalui serangkaian proses belajar yang pada akhirnya akan menghasilkan perubahan tingkah laku pada individu tersebut. Proses pembelajaran di sekolah lebih cenderung menekankan pada pencapaian perubahan aspek kognitif (intelektual) yang dilaksanakan melalui berbagai bentuk pendekatan, strategi, dan model pembelajaran tertentu. Sistem pembelajaran yang secara khusus mengembangkan kemampuan afektif kurang mendapat perhatian, kemampuan afektif hanya dijadikan sebagai efek pengiring (nurturant effect). Penelitian ini bertujuan untuk (1) mengetahui apakah pembelajaran online mampu memunculkan kemampuan afektif calon guru prodi (2) menganalisis kemampuan afektif calon guru SD pada pembelajaran online. Data yang digunakan dalam penelitian ini yaitu kualitatif. Teknik yang digunakan ialah angket. Yang diberikan kepada 132 responden, Hasil penelitian menunjukkan bahwa kemampuan afektif dapat muncul pada pembelajaran online. Indikator kemampuan afektif dalam penelitian ini, meliputi sikap, minat, konsep diri, nilai, dan moral yang semuanya berada pada rentang baik. Hal ini berarti bahwa hasil kemampuan afektif calon guru sekolah dasar dapat dikatakan valid atau muncul pada pembelajaran online. Kata Kunci: Kemampuan Afektif; e-learning; PGSD